The Impact of Quantum Teaching Strategy on the Academic Achievements of Students in Inclusive Schools - Gunarhadi (2010)
The research was aimed (1) to measure the impact of Quantum Teaching Strategy (QTS) on the academic achievements of Bahasa Indonesia, Science, and Mathematics, (2) to measure the impact of QTS on the academic achievements of Bahasa Indonesia, Science, and Mathematics controlled by each of cognition, motivation, and self-esteem, (3) to measure the impact of QTS in comparison to CTS (Conventional Teaching Strategy) on the achievements of the respective subject matter controlled by each of cognition, motivation, and self-esteem, (4) to measure the difference of impact of QTS on each of subject matter compared to the other, and (5) to qualitatively measure the pertaining effects of QTS on both academic and non-academic performances. Achievement tests on the three subject matters and psychological tests on cognition, motivation, and self-esteem were used to collect the academic and non academic primary data. The sample of this research was of intact groups consisting of 68 sixth graders taken from two inclusive elementary schools in the District of Boyolali, Central Java. To determine the location of the research setting and to assign the subjects for the experiment and control groups, cluster random sampling was applied. The research was primarily quantitative, but supported by interviews. In term of quantitative approach, quasi-experiment design was used to describe the different results of academic achievement between the experiment and control groups. T-Test and ANCOVA were statistically used to analyse the data. T-Test was used to measure the impact of Quantum Teaching Strategy (QTS) in comparison to Conventional Teaching Strategy (CTS) on the three subject matters, whereas ANCOVA was to measure the impact of QTS in comparison to CTS on three subject matters controlled by cognition, motivation, and self-esteem. For further measure of impact resulted from the quasi-experiment, interviews were also applied as to explore the effect of the treatment of QTS among particular students with special needs in their real setting. By means of T-Test and ANCOVA, the findings showed that(1)QTS significantly affected the academic achievements of Bahasa Indonesia, Science and Mathematics, (2) QTS significantly affected the academic achievements of Bahasa Indonesia, Science and Mathematics controlled by either cognition, motivation or self-esteem, (3) QTS affected the academic achievements differently from CTS on Bahasa Indoensia, Science, and mathematics controlled by either cognition, motivation or self-esteem, (4) Covariate cognition, motivation, or self-esteem affected differently on the academic achievements of the three subjet matters, and (5) the finding from interviews study showed that QTS indirectly affected the non-academic performance of students with special needs.